Bilateral agreement for the academic year 2010/2011, 2012/2013 Lifelong Learning Programme: higher education between Universitat Politècnica de València and Universidade Lusíada de Lisboa - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within the Lifelong Learning Programme. - Subject area: Architecture, urban and regional planning.